2011
DOI: 10.1364/oe.19.016126
|View full text |Cite
|
Sign up to set email alerts
|

Random lasing from granular surface of waveguide with blends of PS and PMMA

Abstract: Lasing from a planar waveguide with the blend of Polystyrene(PS): Poly-methylmethacrylate(PMMA) doped with tris(8-hydroxyquinolinato)aluminum(Alq(3)) and 4-(dicyanomethylene)-2-tert-butyl-6(1,1,7,7-tetramethyljulolidyl-9-enyl)-4H-pyran(DCJTB) was investigated. Due to phase separation of the blend of PS:PMMA during the solvent evaporation process, a waveguide with granular surface was obtained, which has 2D island-like nanostructures with diameters ranging between 200 and 400 nm and heights at about 25 nm. Pump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 28 publications
(32 reference statements)
0
14
0
Order By: Relevance
“…6 Here, l s , scattering mean free path, is dened as the average distance that light travels between two consecutive scattering events, and l g , amplication length, is inversely proportional to the optical gain. A variety of nanomaterials, such as semiconductor, 7 dielectric materials, 8 polymer, 9 human tissue, 10 plant structures, 11 and biological tissues 12 have been demonstrated to generate RLs. Owing to their intrinsic birefringence, liquid crystals (LCs) 13 are considered as a superior light scattering material for RLs.…”
Section: Introductionmentioning
confidence: 99%
“…6 Here, l s , scattering mean free path, is dened as the average distance that light travels between two consecutive scattering events, and l g , amplication length, is inversely proportional to the optical gain. A variety of nanomaterials, such as semiconductor, 7 dielectric materials, 8 polymer, 9 human tissue, 10 plant structures, 11 and biological tissues 12 have been demonstrated to generate RLs. Owing to their intrinsic birefringence, liquid crystals (LCs) 13 are considered as a superior light scattering material for RLs.…”
Section: Introductionmentioning
confidence: 99%
“…Several discrete narrow peaks (i.e., lasing modes) started to emerge as the pump power exceeded the laser threshold, which indicated that resonant feedback was generated in the POFRL. According to the previous studies, RLs with resonant (field or amplitude) feedback are categorized as coherent RLs . The FWHM of the lasing mode narrowed down to 0.5 nm, which is two orders of magnitude narrower than the FWHM of the spontaneous emission peak.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of an ASE threshold also determines the film's compatibility as a gain medium and allows us to measure the gain and loss coefficients. For the ASE measurements, we follow the procedure commonly used for examine organic semiconducting gain materials [29], whereby we excited the film with a stripe-shaped beam in 1.6 x 0.4 mm 2 dimension and detect the emission from the edge of the film. The long axis of the beam is oriented perpendicular to the edge of the sample where the emission is monitored, thereby forming a gain-guide which transports the spontaneously emitted light to the edge of the film while getting amplified along the way.…”
Section: Resultsmentioning
confidence: 99%